Sites and politics of religious diversity in Southern Europe : the best of all gods - Mapril, José. (International Studies in Religion and Society, 2013)
In recent years, the Southern borders of Europe have become landmarks for the mediatic and academic verve regarding the migration and diasporas towards and beyond 'Schengen Europe'. In these debates, religion is acknowledged as playing a central role in the recognition of major societal changes in the continent, being object of political concern and attention: from the recognition of plural forms of Christianity to the debates on a 'European Islam'. Yet, in this respect, what goes on around the borders of Portugal, Spain, Italy or Greece is still largely uncharted and un-debated. With the contribution of renowned anthropologists, sociologists and religious studies scholars, this book critically presents and discusses case studies on the sites and politics of religious diversity in Southern Europe, including the impact of migrant religiosity in national and EU politics.